2001
DOI: 10.1046/j.1365-2761.2001.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass mortality associated with a Sphaerospora‐like myxosporidean infestation in juvenile cobia, Rachycentron canadum (L.), marine cage cultured in Taiwan

Abstract: Cultured cobia, Rachycentron canadum, of 45±80 g exhibited anaemia and ascites, and a mottled red and grey, extremely enlarged kidney with cream-coloured patches or spherical nodules. Cumulative mortality was about 90% within 1 month. Extrasporogonic or sporogonic stages of a myxosporean appeared in the blood, glomerulus, renal tubules and renal interstitium. The renal tubules were the main target tissue of the parasite and were completely occluded by sporogonic pseudoplasmodia at various degrees of maturity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Cobia is a newly farmed fish in mariculture, only a few pathological studies have been conducted in that species (Chen et al . ). The majority of marine fishes cultured in cages are susceptible to vibriosis, with some fish species more sensitive to the infection than others.…”
Section: Resultsmentioning
confidence: 97%
“…Cobia is a newly farmed fish in mariculture, only a few pathological studies have been conducted in that species (Chen et al . ). The majority of marine fishes cultured in cages are susceptible to vibriosis, with some fish species more sensitive to the infection than others.…”
Section: Resultsmentioning
confidence: 97%
“…Concurrently, a more proactive culture strategy for cobia was adopted, aimed at combating the vulnerability of practically all life stages of cobia to bacterial diseases and parasitic infections with prophylactic treatments (Chen, Kou, Wu, Wang & Su 2001; Rajan, Lopez, Lin & Yang 2001; Lopez, Rajan, Lin, Kuo & Yang 2002; Rajan, Lin, Ho & Yang 2003; Ho, Kim, Cruz‐Lacierda & Nagasawa 2004; Liu, Lin, Chuang & Lee 2004; Lin, Chen, Chen, Chen, Chou, Chen, Su & Yang 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Net cage culture of cobia started in Taiwan in 1995 and yielded 4,186 metric tons in 2003 according to the FAO statistics. Because of its short culture history, reports on the diseases of cobia are quite limited, including viral, bacterial and parasitic infections (Chen et al, 2001;Chi et al, 2003;Lopez et al, 2002;Rajan et al, 2001). A Sphaerospora-like myxozoan in the kidney and monogenean Neobenedenia sp.…”
mentioning
confidence: 99%
“…A Sphaerospora-like myxozoan in the kidney and monogenean Neobenedenia sp. on the body surface have been known as parasitic agents (Chen et al, 2001;Lopez et al, 2002). Lopez et al (2002) reported that Neobenedenia sp.…”
mentioning
confidence: 99%